'A flood of Syrians has slowed to a trickle': The use of metaphors in the representation of Syrian refugees in the online media news reports of host and non-host countries. Issue 2 (April 2017) - Abid, Raith Zeher; Manan, Shakila Abdul; Rahman, Zuhair Abdul Amir Abdul
Numerous studies have examined the manner in which minority groups, including refugees, are depicted in the media discourse of the host countries or the dominant majority groups. The results of such studies indicate that media systematically discriminate these minority groups and deem them as a security, economic and hygiene threat to the majority groups. Through the use of Lakoff and Jonson's conceptual metaphor theory, this study compares and contrasts the representation of Syrian refugees in the online media discourse of not only host countries but also non-host countries, which, in this study, refers to nations that do not host Syrian refugees. The results show that statistical differences between the metaphors used by host and non-host countries only occur when using the metaphors that describe the entry of refugees and the burden they are inflicting on the host countries. This is clearly indicated by the p -values of the log-likelihood test.